Epidemiologic studies and novel clinical research approaches that impact TB vaccine development - Evans, T. G.; Churchyard, G. J.; Penn-Nicholson, A.; C. Chen; Gao, X.; Tait, D. R.; Hatherill, M. (Tuberculosis (Edinb), 2016)
The 4th Global Forum on TB Vaccines, convened in Shanghai, China, from 21 - 24 April 2015, brought together a wide and diverse community involved in tuberculosis vaccine research and development to discuss the current status of, and future directions for this critical effort. This paper summarizes the sessions on Developing TB Vaccines for Prevention of Disease, Prevention of Infection, and Immunotherapy Indications; Concepts and Approaches in Clinical Research & Development; and Epidemiological Research. Summaries of all sessions from the 4th Global Forum are compiled in a special supplement of Tuberculosis.
Keywords: BCG Vaccine Drug Discovery Epidemiologic Methods Humans Secondary Prevention Tuberculosis/epidemiology/*prevention & control *Tuberculosis Vaccines *Clinical trial *Epidemiology *Tuberculosis